2021
DOI: 10.1007/s13224-021-01482-1
|View full text |Cite
|
Sign up to set email alerts
|

Respectful Maternity Care Initiative: A Qualitative Study

Abstract: Aim To assess the available standards for respectful maternity care in a public maternity hospital by evaluation of responses to a questionnaire given to birthing women. Methodology Assessment was done to find out the level of respectful maternity care provided under the most sensitive and important areas, namely (1) confidentiality and privacy, (2) physical harm or ill treatment, (3) dignity and respect, (4) left without care, (5) right to information, informed consent, and choice/preferences, by obtaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Most of the females in this study reported that they were never encouraged to call for help when in need and that the staff did not respond quickly, which is consistent with the findings of other studies [ 17 , 25 , 26 ]. This untoward occurrence might be due to the over-exhaustion of the nursing staff, as the recommended staff-to-patient ratio is difficult to maintain in a public setup.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the females in this study reported that they were never encouraged to call for help when in need and that the staff did not respond quickly, which is consistent with the findings of other studies [ 17 , 25 , 26 ]. This untoward occurrence might be due to the over-exhaustion of the nursing staff, as the recommended staff-to-patient ratio is difficult to maintain in a public setup.…”
Section: Discussionsupporting
confidence: 90%
“…The literature review did not yield any studies that dealt with all the components of the 2018 WHO intrapartum care model. Moreover, few qualitative studies were conducted on this subject, most of which were not comprehensive and discussed only some components of this model such as respectful maternal care and continuity of care ( 22 24 ). In line with the population policies of the Iranian government and the promotion of intrapartum care, this study on the 2018 WHO intrapartum care model is expected to lead to an increase in women's positive experiences of labor and their desire for giving birth to another child through normal vaginal delivery and also to reduce the rate of unnecessary cesarean sections.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined in the intrapartum care recommendations of the WHO, the experience of the care is as crucial as providing clinical care in reaching the desired individual-based results [ 8 ]. However, non-clinical measures during childbirth, such as providing emotional support via companionship, effective communication, and respectful care—which may be relatively inexpensive, are not considered priorities in many healthcare centers [ 9 ]. Similarly, obstetric options that respect women’s values and promote decision-making in childbirth’s first and second stages are not constantly provided.…”
Section: Introductionmentioning
confidence: 99%